Plants Attract Parasitic Wasps to Defend Themselves against Insect Pests by Releasing Hexenol - Wei, Jianing (Public Library of Science, 2007)
BACKGROUND: Plant volatiles play an important role in defending plants against insect attacks by attracting their natural enemies. For example, green leaf volatiles (GLVs) and terpenoids emitted from herbivore-damaged plants were found to be important in the host location of parasitic wasps. However, evidence of the functional roles and mechanisms of these semio-chemicals from a system of multiple plants in prey location by the parasitoid is limited. Little is known about the potential evolutionary trends between herbivore-induced host plant volatiles and the host location of their parasitoids. METHODOLOGY/PRINCIPAL FINDINGS: The present study includes hierarchical cluster analyses of plant volatile profiles from seven families of host and non-host plants of pea leafminer, Liriomyza huidobrensis, and behavioral responses of a naive parasitic wasp, Opius dissitus, to some principal volatile compounds. Here we show that plants can effectively pull wasps, O. dissitus, towards them by releasing a universally induced compound, (Z)-3-hexenol, and potentially keep these plants safe from parasitic assaults by leafminer pests, L. huidobrensis. Specifically, we found that volatile profiles from healthy plants revealed a partly phylogenetic signal, while the inducible compounds of the infested-plants did not result from the fact that the induced plant volatiles dominate most of the volatile blends of the host and non-host plants of the leafminer pests. We further show that the parasitoids are capable of distinguishing the damaged host plant from the non-host plant of the leafminers. CONCLUSIONS/SIGNIFICANCE: Our results suggest that, as the most passive scenario of plant involvement, leafminers and mechanical damages evoke similar semio-chemicals. Using ubiquitous compounds, such as hexenol, for host location by general parasitoids could be an adaptation of the most conservative evolution of tritrophic interaction. Although for this, other compounds may be used to improve the precision of the host location by the parasitoids.